2019
DOI: 10.1111/cen.14041
|View full text |Cite
|
Sign up to set email alerts
|

Changes in body composition in male adolescents with childhood‐onset GH deficiency during transition

Abstract: Objective Restarting rhGH in adolescents with childhood‐onset (CO‐) GHD is usually based on GH retest, IGF‐1, additional pituitary hormone deficiencies, pituitary morphology and history. Short‐term changes in body composition in adolescents with CO‐GHD when off rhGH may contribute to the identification of those in need of treatment continuation. Design This is a longitudinal single‐centre study. Patients and measurements The body composition of 90 male adolescents with low‐likelihood severe GHD of adolescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…After the first screening, based on title and abstract, 52 full-text articles were selected for assessment of eligibility. After this second screening process, a total of 15 articles were considered eligible for this review ( 17 31 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the first screening, based on title and abstract, 52 full-text articles were selected for assessment of eligibility. After this second screening process, a total of 15 articles were considered eligible for this review ( 17 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies did not specify which stimulation tests were used ( 19 , 21 , 22 , 27 29 ). The diagnosis of GHD was based on a peak GH value of <10 ng/mL in eight studies ( 17 , 20 , 22 , 24 27 , 29 ), <5 ng/mL in one study ( 31 ), and <3 ng/mL in another ( 18 ). The maximum GH concentration limit required for a diagnosis of GHD was not specified in five studies ( 19 , 21 , 23 , 28 , 30 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, patients’ BMI Z-scores increased, whereas their IGF-1 and IGFBP-3 levels decreased during the GH treatment interruption period; however, their BMI Z-scores did not improve even after 1 year of GH replacement therapy. Several studies have reported that GH treatment discontinuation during the transition period led to an increase in BMI [ 23 ] and fat mass, in addition to a decrease in lean body mass [ 11 , 24 , 25 ]. Although the present study could not evaluate the body composition in detail, the increased BMI Z-scores in the cohort suggest that GH treatment discontinuation influences adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance to our results, other studies demonstrated that recommencement of rhGH in TP with the duration of 1–2 years manifested as significant LBM increase (6–14%) and FM reduction (7–12%). Discontinuation of rhGH treatment for 6–24 months in COGHD adolescents after final height achievement resulted in FM increase (10–17%) and LBM decrease by up to 8% ( 3 , 8 , 30 , 31 , 32 , 33 , 34 , 35 ). By contrast, a few studies reported no difference in BC parameters after 6–24 months period of rhGH after growth completion ( 4 , 36 ).…”
Section: Discussionmentioning
confidence: 99%